PENGARUH PENDIDIKAN KARAKTER DALAM KELUARGA TERHADAP KEDISIPLINAN SHALAT LIMA WAKTU SISWA KELAS XI SMK PATRIOT PETERONGAN JOMBANG - Rofi’atul Hidayah; Muhtadi; Adibah Jauhari (FAI- Undar, 2021)
This research is to determine whether there is influence character in family education to the discipline of prayer five times Class XI student of SMK Patriot Peterongan Jombang. This type of research is a quantitative study with statistical analysis test product moment correlation. The population in this study is the parents and the students of Class XI SMK Patriot Peterongan Jombang. Character education in family becomes the independent variable (X) and the discipline of prayer faive times Class XI student of SMK Patriot Peterongan Jombang be the dependent variable (Y). Data on these two variables was obtained from the questionnaire enclosed.From the above data it is known that character education in family and discipline of praying five times Class XI student of SMK Patriot Peterongan Jombang, by using product moment the result was 0.539 for a specified confidence level of 95% and N = 80, then rtabel = 0.220. Turns rhitung greater than the price rtabel, then Ho is rejected and Ha accepted. In accordance with the interpretation of the correlation coefficient table that the value of 0.539 in the category level of a very strong relationship. It can be concluded that